PEMBATALAN SEPIHAK DALAM PERJANJIAN SEBAGAI PERBUATAN MELAWAN HUKUM - Yohanes Suhardin (LPPM Universitas Katolik Santo Thomas Medan, 2025)
An agreement is an agreement between two or more parties that creates reciprocal rights and obligations. However, in practice, unilateral cancellations are often carried out by one of the parties without a valid legal basis. This action can be categorized as an unlawful act if it meets the elements specified in Article 1365 of the Civil Code. This research aims to analyze unilateral cancellation of agreements from a civil law perspective and determine the conditions under which unilateral cancellation can be considered an unlawful act. The method used is a normative juridical approach with a literature study of statutory regulations and court decisions. The research results show that unilateral cancellation carried out without good faith and not fulfilling legal requirements can cause losses to other parties and thus constitutes an unlawful act. Legal enforcement of this act is important to provide legal certainty and protection for the parties to the agreement.